Azimuthally unidirectional transport of energy in magnetoelectric fields: topological Lenz's effect. Issue 21 (30th November 2017) - Joffe, R.; Kamenetskii, E. O.; Shavit, R.
Abstract: Magnetic-dipolar modes (MDMs) in a quasi-2D ferrite disc are microwave energy-eigenstate oscillations with topologically distinct structures of rotating fields and unidirectional power-flow circulations. At the first glance, this might seem to violate the law of conservation of an angular momentum, since the microwave structure with an embedded ferrite sample is mechanically fixed. However, an angular momentum is seen to be conserved if topological properties of electromagnetic fields in the entire microwave structure are taken into account. In this paper, we show that due to the topological action of the azimuthally unidirectional transport of energy in a MDM-resonance ferrite sample there exists the opposite topological reaction on a metal screen placed near this sample. We call this effect topological Lenz's effect. The topological Lenz's law is applied to opposite topological charges: one in a ferrite sample and another on a metal screen. The MDM-originated near fields – the magnetoelectric (ME) fields – induce helical surface electric currents and effective charges on a metal. The fields formed by these currents and charges will oppose their cause.